A study on the correlation between seat selection and interaction preference in virtual-reality fusion simulation experiment - Chen, Shihan; Luo, Yuan; Zhang, Hao; Liu, Xiaohong (Frontiers in Psychology, 2022)
In order to explore the correlation between students’ seat choice and interaction preference in the open gamification scenario, an experiment has been carried out on the platform of provincial virtual simulation experiment teaching center of a university , and tested the relationship between absolute distance, seat type, workstation type and students’ interaction preference. The results show that in the virtual-reality fusion gamification scenario where students can move freely: (1) The inner circle students can stimulate the outer circle students’ willingness to invest in learning. (2) The task attribute and the seat distribution of the group may lead to the difference of students’ interaction preference. (3) Students are more likely to learn knowledge and skills by interacting with “people” rather than “object”. (4) Gender and major influence students’ experience of participating in gamified teaching. The results confirm that the interactive engagement effect of location does exist in immersive virtual-reality fusion gamification teaching scenario, and suggestions are put forward to adjust the effect of location through instructional design and teacher intervention.